Mutualist Microfinance Informal Savings Funds from the Global Periphery to the Core? - Swaan de, Abram (Aksant Academic Publishers, 2006)
Small mutual funds once flourished in nineteenth century Europe and North America. They still abound in Asia, Africa and Latin America. In recent years they have come back to European and North American cities with the immigrants from the global South. Some of the small mutual savings funds use the accumulated sums to provide financial assistance to members in distress and thus fulfil an insurance function. Others make loans regardless of their members' individual needs, in which case it is the savings or credit function that predominates. In this volume, five authors describe and analyse the results of their fieldwork among mutual fund members in Hyderabad, Yogyakarta, Ayelitsa (a township near Cape Town), among Surinamese in both Paramaribo (Suriname) and Amsterdam, as well as among Senegalese Peul who migrate from Thilonge to Dakar and on to Paris. The studies are based on field observations and personal interviews. The two editors, Abram de Swaan and Marcel van der Linden, provide a common comparative approach, and a shared historical and theoretical perspective. The essays explore the varieties and the logic of mutual funds, emphasizing the importance of peer pressures as a 'social constraint' to increase 'self constraint' on spending. Cooperation in a mutual fund, whether for insurance or saving purposes, can proffer the participants advantages which they cannot realize on their own.